HADIS TENTANG ADAB PESERTA DIDIK DAN RELEVANSINYA DALAM PENDIDIKAN KONTEMPORER - Windary Sri Patimah; Iskandar Mirza (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
The phenomenon of moral degradation (adab) among students in contemporary education such as declining learning ethics, reduced respect for teachers, and weakened academic responsibility has become a serious challenge in Islamic education. This condition calls for the reinforcement of adab values derived from Islamic teachings, particularly the hadiths of the Prophet Muhammad (peace be upon him). This paper aims to analyze hadiths related to student etiquette (adab) and their relevance in the context of contemporary Islamic Religious Education (PAI). The method used is qualitative research with a library research approach, employing thematic (maudhu’i) analysis of educational (tarbawi) hadiths, along with a review of Islamic education literature and contemporary educational theories. The objectives of this study are to identify the prophetic hadiths that explain student etiquette, to examine the values of adab contained within these hadiths, and to explore their relevance in contemporary education.The findings indicate that values of student adab such as sincerity, diligence in seeking knowledge, humility (tawadhu’), patience, and respect for teachers have strong relevance in shaping students’ character and academic ethics. The integration of these values into PAI learning can strengthen the function of Islamic education as a means of developing individuals who are morally upright, moderate, and socially responsible. Thus, student adab based on hadith serves as a fundamental foundation for strengthening character education in the contemporary era. ABSTRAKFenomena degradasi adab peserta didik dalam pendidikan kontemporer, seperti menurunnya etika belajar, sikap hormat kepada guru, dan tanggung jawab akademik, menjadi tantangan serius dalam dunia pendidikan Islam. Kondisi ini menuntut penguatan kembali nilai-nilai adab yang bersumber dari ajaran Islam, khususnya hadis Nabi Muhammad SAW. Makalah ini bertujuan untuk menganalisis hadis-hadis tentang adab peserta didik serta relevansinya dalam konteks Pendidikan Agama Islam (PAI) masa kini. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi pustaka (library research), melalui analisis tematik (maudhu’i) terhadap hadis-hadis tarbawi serta kajian literatur pendidikan Islam dan teori pendidikan kontemporer. Tujuan dari penelitiana ini Adalah untuk mengetahui apa saja hadits nabi yang menjelaskan tentang adab peserta didik, mengetahui bahagiaman nilai-nilai adab peserta didik dalam hadits, dan relevansinya dalam Pendidikan kontemporer. Hasil kajian menunjukkan bahwa nilai-nilai adab peserta didik, seperti keikhlasan, kesungguhan dalam menuntut ilmu, tawadhu’, kesabaran, dan penghormatan kepada guru, memiliki relevansi yang kuat dalam pembentukan karakter dan etika akademik peserta didik. Integrasi nilai-nilai tersebut dalam pembelajaran PAI dapat memperkuat fungsi pendidikan Islam sebagai sarana pembentukan manusia berakhlak mulia, moderat, dan bertanggung jawab secara sosial. Dengan demikian, adab peserta didik berbasis hadis menjadi fondasi penting dalam penguatan pendidikan karakter di era kontemporer.